(untitled) (Journal of Shaheed Suhrawardy Medical College, 2012)
Objective: To assess socio-epidemiology of Antepartum Fetal Death IAFD) in a tertiary hospital in Bangladesh. Method: Fifty three pregnant women with intra-uterine fetal death before or after delivery were interviewed in Gvnaecologv in-patient of Dhaka Medical College Hospital during 2004-2005. In this cross sectional study selected socio-demographic factors like age, education, occupation, income etc. and epidemio/ogic factors like previous stillbirth or congenital anomaly history, antenatal history, and other medical conditions like gestational diabetes and pregnancy induced hypertension were sought. Results: Respondents were young (25.15 ± 6.45), married at an earlier age (18.51 ± 2.85), majority (62.26%) got pregnant at <=20 years and more than 50% were primigravid. Most (84.9%) of the respondents were either illiterate or low educated whereas 53% of the husbands were so. Nearly 70% worked more than 8 hours a day, almost half had low family income. History of stillbirth (13.21%>) and congenital anomaly (9.43%) in previous pregnancy were also found with AFD. More than half (29, 54.7%) of the respondents did not take ANC during this pregnancy. Only 3 respondents had gestational diabetes and 7 had pregnancv induced hypertension. Conclusion: Increasing the age at marriage and pregnancy, education, adequate rest during pregnancv and off course, increasing coverage of ANC could bring about satisfactory outcome if taken care of before future pregnancies. Journal of Shaheed Suhrawardy Medical College Vol 2No.1 June 2010 page 13-16 DOI: http://dx.doi.org/10.3329/jssmc.v2i1.12345